INSPIRE Geology Data Model Implementation in Digital Geological Map Production in Portugal - Pereira, Aurete (2018)
Pereira, A., Luís, G., & Cabral, P. (2013). INSPIRE Geology Data Model Implementation in Digital Geological Map Production in Portugal: A Preliminary Approach. International Journal of Spatial Data Infrastructures Research, 8, 128-143. DOI: 10.2902/1725-0463.2013.08.art6